Demographics and serological profile of blood donors who opt for the confidential unit exclusion in a blood bank in Sao Paulo, Brazil - Delatorre, Marcella Vizcaya Val; Batalha, Kalyne M.; Santos, Leandro Dinalli; Bonet-Bub, Carolina; Avelino-Silva, Vivian Iida (Revista do Instituto de Medicina Tropical de São Paulo, 2021)
Blood transfusion is still an irreplaceable therapeutic modality, widely applied to medical care. Clinical interviews and laboratory testing for transfusion-transmitted infections (TTI) are routinely performed to prevent TTI among the recipients. However, there is still a residual risk of TTI, and some blood banks have adopted the confidential unit exclusion (CUE) as an additional safety strategy. In this study, we investigated the demographic characteristics and laboratory results of the screening of TTI among blood donors who opted for the CUE, compared to blood donors who did not opt for the CUE. In this study, we included 32,261 blood donations collected in a single blood bank in Sao Paulo, Brazil. A very small proportion of donors (0.25%) opted for the CUE. They were mainly single males and were more likely to have HBV, syphilis, and other positive results in the combined screening for TTI, in comparison with those who did not opt for the CUE. This difference was statistically significant in both the univariable and the multivariable analysis adjusted for age, gender , marital status and years of schooling. Our findings highlight that CUE may be a useful tool to improve the safety for blood recipients, but its efficiency is context-dependent.